2017
DOI: 10.1097/wnf.0000000000000209
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcoated Perineuronal Nets Regulate “GABAergic” Transmission: Bittersweet Hypothesis in Autism Spectrum Disorder

Abstract: Fast-spiking, parvalbumin-expressing "GABAergic" interneurons regulate synchronous oscillatory output of pyramidal neurons. Metabolic demands of these GABAergic projections are great because local ion concentrations must be optimally maintained; in addition, high rates of mitochondrial respiration necessitate exquisite redox regulation. Interestingly, only fast-spiking, parvalbumin-expressing basket cells coexpressing 3 metalloproteinases seem to be preferentially enwrapped in perineuronal nets (PNNs), a speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 35 publications
0
40
0
Order By: Relevance
“…Impaired adult neurogenesis is present in many neuropsychiatric and neurodegenerative disorders (Aimone et al 2014; Besnard and Sahay 2016; Burket et al 2017; Kang et al 2016; Lazarov and Marr 2010), and it has been proposed that improving adult neurogenesis could be therapeutic (Jin et al 2004). α7 nAChR dysfunction has been linked to many of these disorders (Dineley et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Impaired adult neurogenesis is present in many neuropsychiatric and neurodegenerative disorders (Aimone et al 2014; Besnard and Sahay 2016; Burket et al 2017; Kang et al 2016; Lazarov and Marr 2010), and it has been proposed that improving adult neurogenesis could be therapeutic (Jin et al 2004). α7 nAChR dysfunction has been linked to many of these disorders (Dineley et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, "downstream" consequences of impaired transport functions of these "Ptype ATPases", such as interference with synthesis and secretion of cuproenzymes, could play roles in pathogenic processes within the CNS. Further, data suggesting that synaptic release of copper modulates NMDA receptor-mediated neurotransmission, and perineuronal nets (PNNs), which are polyanionic, lattice-like embellishments of the extracellular matrix (ECM), bind redox-reactive metals, such as copper and iron, arouse additional interest in possible regulatory and pathogenic roles of copper in CNS [12][13][14]. PNNs enwrap subpopulations of fast-spiking, parvalbumin-expressing (FS, PV+) GABAergic inhibitory basket cells and pyramidal cells in the neocortex, which are neural elements implicated in the pathogenesis of several major neuropsychiatric disorders, including ASD and schizophrenia [13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, redox-reactive copper is an essential element required for normal CNS function and implicated in pathogenic mechanisms, including disruption of synaptic transmission. Increasingly, physicochemical studies of perineuronal nets (PNNs) and their isolated structural components inform possible functional roles of PNNs in the CNS, such as maintenance of the fast-spiking properties of a subset of parvalbumin-expressing GABAergic interneurons, and modulation of local temporal fluctuations in the binding of redox-reactive metals and their participation in scavenging of toxic free radical species [12,13,19]. The "Donnan-type distribution" of ions created by the "ionic sorting" property of PNNs surrounding fast-spiking parvalbumin-expressing GABAergic Basket cells contributes to generating high-frequency action potentials by pushing Clinward and pulling K + outward [13,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the role of the ECM in age-related neuroplasticity has also produced interesting results. Fox et al have shown that, in animals, the previously lost neuroplasticity in visual cortex areas is recovered after the administration of chondroitinase ABC, which enables interneural communication by degrading ECM [126].…”
Section: Perineuronal Nets - Clinical Aspectsmentioning
confidence: 99%